Staphylococcus aureus and Aspergillus Funigatus infections In Making Animal Models of Rhinosinusitis - Renny Wijayanti; Andriana Tjitria Widi Wardani; Agung Sulistyanto (Jurnal Litbang Edusaintech, 2022)
Rhinosinusitis is an inflammation of the mucosa or mucous membranes of the nose and sinuses, the most common being maxillary sinusitis and ethmoid sinusitis, while frontal sinusitis and sphenoid sinusitis are less common. Rhinosinusitis is caused by any condition that blocks the flow of mucus from the sinuses to the nasal cavity. If rhinosinusitis is not treated or does not heal completely, it can cause several complications for the patient such as infection of the brain, infection / swelling of the tissue around the eyeball, decreased vision function, bone infection around the sinuses, pus coming out of the face, changes in facial shape / protruding / swelling, and sore throat often recur. The main purpose of the medical system in Islam is to maintain health rather than cure disease. Sinusitis that is not immediately treated can also cause permanent loss of the sense of smell. Usually sinusitis is treated with medication. But in certain cases, sinusitis must be treated with surgery. The animal model of rhinosinusitis was made by blocking the right nares of rats by using Merocel tamponade. Then an incision is made in the skin, superior to the maxillary sinus. Intraperitoneal induction and intranasal induction 0.1 ml of a solution of Streptococcus aureus type 1, consisting of 107-109 S. aureus/ml, and Aspergillus Fungigatus 107-109/ml were inoculated into the right maxillary sinus. The same amount of physiological saline was also injected into the left maxillary sinus as a control agent. Rhinosinusitis is an inflammation of the mucosa or mucous membranes of the nose and sinuses, the most common being maxillary sinusitis and ethmoid sinusitis, while frontal sinusitis and sphenoid sinusitis are less common. Rhinosinusitis is caused by any condition that blocks the flow of mucus from the sinuses to the nasal cavity. If rhinosinusitis is not treated or does not heal completely, it can cause several complications for the patient such as infection of the brain, infection / swelling of the tissue around the eyeball, decreased vision function, bone infection around the sinuses, pus coming out of the face, changes in facial shape / protruding / swelling, and sore throat often recur. The main purpose of the medical system in Islam is to maintain health rather than cure disease. Sinusitis that is not immediately treated can also cause permanent loss of the sense of smell. Usually sinusitis is treated with medication. But in certain cases, sinusitis must be treated with surgery. The animal model of rhinosinusitis was made by blocking the right nares of rats by using Merocel tamponade. Then an incision is made in the skin, superior to the maxillary sinus. Intraperitoneal induction and intranasal induction 0.1 ml of a solution of Streptococcus aureus type 1, consisting of 107-109 S. aureus/ml, and Aspergillus Fungigatus 107-109/ml were inoculated into the right maxillary sinus. The same amount of physiological saline was also injected into the left maxillary sinus as a control agent.